Numerical Analysis of Heat Transfer in U-Shaped Flow Around a Rotating Circular Cylinder in a 3D Print Filament Dryer - Afrijal, Agung; Maghfurah, Fadwah (Suara Teknik : Jurnal Ilmiah, 2025)
The flow past rotating circular cylinders has been extensively studied, primarily focusing on crossflow phenomena. To explore alternative flow patterns, this study investigates U-shaped flow and heat transfer around a rotating circular cylinder, simulating the drying process in a 3D-print filament dryer. Numerical simulations were performed using the rhoSimpleFoam solver in OPENFOAM 2306 to analyze flow and heat transfer characteristics. The inlet flow had a Reynolds number of 2000, with constant temperatures of 50°C at the inlet chamber and 20°C at the cylinder surface. Cylinder rotation speeds ranged from 0 to 4. The results showed that higher cylinder rotation speeds lead to a more uniform heat transfer distribution along its circumference, consistent with findings in crossflow studies. However, a key difference observed in the U-shaped flow is that higher rotation speeds also resulted in increased average heat transfer, contrasting prior studies on crossflow phenomena, which reported the opposite trend. These results are expected to have a positive impact on the development of 3D-print filament dryers, which enables a drying process that ensures uniformity and high heat transfer. Additionally, a validation simulation demonstrated good agreement with previous studies.